Chicken adaptive response to nutrient density: immune function change revealed by transcriptomic analysis of spleen - Zhou, Yan; Cao, Dingguo; Liu, Jie; Li, Fuwei; Han, Haixia; Lei, Qiuxia; Liu, Wei; Li, Dapeng; Wang, Jie (Frontiers in Immunology, 2023)
Abstract Feed accounts for the largest portion (65-70%) of poultry production costs. The feed formulation is generally improved to efficiently meet the nutritional needs of chickens by reducing the proportion of crude protein (CP) and metabolizable energy (ME) levels in the diet. Although many studies have investigated the production performance during dietary restriction, there is a lack of research on the mechanisms by which immune cell function is altered. This study examined the effects of ME and CP restriction in the chicken diet on serum immunoglobulins and expression of immune function genes in spleen. Changes in serum immunoglobulins and immune-related gene expression were analyzed in 216 YS-909 broilers fed with 9 different dietary treatments, including experimental treatment diets containing low, standard, and high levels of ME or CP in the diet. At 42 days of age, serum immunoglobulins and expression of spleen immune genes in 6 female chickens selected randomly from each dietary treatment (3×3 factorial arrangement) group were measured by enzyme-linked immunosorbent assay (ELISA) and transcriptomic analysis using RNA sequencing, respectively. The results showed that the IgM level in the low ME group chickens was significantly (p < 0.05) lower than that in other groups. In addition, immune-related genes, such as MX1, USP18, TLR4, IFNG and IL18 were significantly upregulated when the dietary nutrient density was reduced, which may put the body in an inflammatory state. This study provided general information on the molecular mechanism of the spleen immune response to variable nutrient density.